PENGETAHUAN PASANGAN USIA SUBUR TENTANG KESEHATAN REPRODUKSI DENGAN PENUNDAAN KEHAMILAN SAMPAI BATAS WAKTU YANG DIINGINKAN - Desi Tricahyani (Akademi Kebidanan Griya Husada Surabaya, 2016)
ABSTRACT Background: readiness and psychological health are very important for both wife and husband. To understand the physical and psychological readiness of husband and wife of childbearing age (PUS), they need knowledge about reproductive health. Increased knowledge about reproductive health will have an impact on stability in decision making in postponing pregnancy. Method: The research design used was non-experimental with a cross sectional correlation approach, the population was all fertile couples in the village of Sidorejo, Pare District Kediri in 2015, using a simple random sampling technique, obtained a sample of 45 people. The study was conducted using questionnaire instruments. The results of data collection were then analyzed using Mann Whitney U test. Results: knowledge of fertile age couples about reproductive health of most respondents who had sufficient knowledge. Delaying the pregnancy until the desired time limit, almost all EFAs delay pregnancy. The results of statistical tests using Mann Whitney U are known that the Z value is equal to -5,519 and P-Value = 0,000. P-Value <? (5%), means that there is a relationship between knowledge of fertile age couples about reproductive health with postponement of pregnancy until the desired time. Conclusion: couples of childbearing age are expected to be able to equip themselves before delaying pregnancy so that they can precisely determine method used